Health-Promoting Lifestyle and Psychosocial Correlates in Patients with NAFLD/MASLD and Family Members: A Comparative Cross-Sectional Study of Independent Samples - Yuhuan Yu; Lili Ji (Healthcare, 2026)
Background/Objectives: Lifestyle modification is central to non-alcoholic fatty liver disease, now termed metabolic dysfunction-associated steatotic liver disease (NAFLD/MASLD), yet comparable health-promoting lifestyle (HPL) data for patients and family members are limited. This study compared two independent samples and examined psychosocial correlates. Methods: Two convenience samples recruited at one tertiary hospital were analyzed: 305 adults with NAFLD/MASLD and 299 adult family members of affected patients. A self-administered electronic questionnaire comprised the Health-Promoting Lifestyle Profile II (HPLP-II), the Self-Rated Abilities for Health Practices scale, autonomous-motivation items from the Treatment Self-Regulation Questionnaire, the Medical Outcomes Study Social Support Survey, and sociodemographic items. Group comparisons used parametric and non-parametric tests. HPL correlates were examined using complete-case regression, HC3 inference, and rank-based sensitivity analysis. Cross-sectional indirect-association decompositions used 5000 bootstrap resamples. Results: HPLP-II scores were 102.2 ± 17.5 in patients and 104.2 ± 17.4 in family members (p = 0.171; Mann–Whitney p = 0.166); the adjusted patient-minus-family difference was −1.14 (HC3 95% CI −3.89 to 1.60; p = 0.413). Physical activity was the lowest-scoring dimension. Self-efficacy was the most robust correlate in both samples; social support was associated in the primary models but weakened under rank transformation in family members. Group-by-correlate interactions were not significant. Exploratory indirect associations through self-efficacy were 0.355 (95% bootstrap CI 0.234–0.512) in patients and 0.163 (0.071–0.287) in family members; reverse-order models were also non-zero. Conclusions: The independent unmatched samples reported similar moderate, physically inactive lifestyles. The results identify associations, not shared-household effects or causal mechanisms; objectively characterized, dyad-matched longitudinal studies are needed.